Projection peculiarities of ecological network in ukraine with consideration of sustainable development conseption - Архіпова, Г.І.; Пушкова, А.М.; Яворська, М.В. (Proceedings of National Aviation University (archive), 2010)
It was considered single integrated system of preservation and rehabilitation of national natural resources. It was paid attention on the projection of the ecological network in Ukraine.